Strong intrinsic multiferroism and magnetoelectric coupling in (1– x )BiFeO 3 –( x )BaTiO 3 films - Tae Yeon Kim; Jesse Schimpf; Atanu Paul; Michael Xu; Atanu Samanta; Sajid Husain; Peter Meisenheimer; Isaac Harris; Peter Finkel; Thomas Mion; Margo Staruch; Anthony J. Ruffino; et al. (Proceedings of the National Academy of Sciences, 2026)
The coexistence of ferroelectric and antiferromagnetic order in BiFeO 3 makes it promising for next-generation magnetoelectric devices. But, single-phase multiferroics with robust room-temperature polarization and magnetization are rare. Here, enhanced, room-temperature ferroelectric polarization (≈ 120 µC cm –2 ), saturation magnetization (≈ 40 emu cm –3 ), and strong magnetoelectric coupling (≈ 400 mV cm –1 Oe –1 ) are observed in epitaxial (1– x )BiFeO 3 –( x )BaTiO 3 thin films. These values of magnetization and magnetoelectric coupling are, respectively, one- and two-orders of magnitude larger than those same properties in the widely studied parent material BiFeO 3 . This sought after combination of properties is found in a distinct tetragonal phase, which is different from rhombohedral and super-tetragonal variants of BiFeO 3 , that emerges at x = 0.2 to 0.3 via combined chemical substitution and epitaxial strain. Structural and physical-property characterization, along with first-principles calculations, reveal a transition from monoclinic to tetragonal symmetry and suggest that short-range ordering of the titanium in the tetragonal phase results in ferrimagnetic spin ordering. This work demonstrates a unique single-phase multiferroic combining strong polarization, magnetization, and magnetoelectric coupling achieved through manipulation of the coupled chemical order and spin order; thereby addressing a major challenge in multiferroics research and providing a path toward practical room-temperature, efficient charge-to-spin and spin-to-charge conversion technologies.